Human genome variation in health and in neuropsychiatric disorders - Buretić-Tomljanović, Alena (Array, 2009)
Variation in the human genome may explain genetic contributions to complex traits and common diseases. Until recently, single nucleotide polymorphisms were thought to be the most prevalent form of interindividual genetic variation. However, structural genomic rearrangements such as deletions, duplications, and inversions lead to variation in gene copy number and contribute even more to genomic diversity. Other sources of genomic variation include noncoding genes, pseudogenes, and mobile genetic elements (transposons). Genome dynamics, including changes in gene number and position as well as epigenetic modifications of coding and noncoding sequences, can affect regulation of gene expression and may contribute to the variability of complex phenotypes